The role of the libero in volleyball as a paradoxical influence on the game: Logical debate and the proposal for a rule change - Eloi, S.; Langlois, V.; Jarrett, K. (The Sport Journal, 2015)
The purpose of this paper is to bring into focus philosophical and logical concerns relating to specific rules that govern the role of the libero in volleyball. The authors contest that the introduction of the position of the libero in volleyball may have actually undermined the continuing logic of the rules of the game. In addressing these questions the authors offer theoretically based rule-change proposals for the sport of volleyball that could be used to inform future training methods or development programmes at both the participatory and elite levels. Discussion may also inform the development of new tools of analysis (e.g. computer software) or the creation of a new breadth of match simulation resources to enhance athlete performance. These tools and devices could then be presented to volleyball coaches in an effort to resolve the issues that have come to light and further inform the philosophical and logical debates about the role of the libero in volleyball.